THE EFFECT OF PINEAPPLE TUBER EXTRACT GEL (Ananas Comosus (L.) Merr) ON COMPOSITE SURFACE ROUGHNESS - Asih Rahaju; Fitriani Indah Dyah Pratiwi (Fakultas Kedokteran Gigi Unjani, 2026)
Teeth whitening using chemicals such as carbamide peroxide can increase the surface roughness of composite resin, which risks causing plaque buildup and secondary caries. Pineapple tubers contain the enzyme bromelain and organic acids known as bleaching alternatif from natural resources whitening effect on the composite with minimal impact on the roughness of the composite. To determine the effect of pineapple tuber extract gel with pH 2.5 and 6.5 on the surface roughness of nanohybrid composites compared to 16% carbamide peroxide. This experimental research used a pre-post test-only controlled group design. A total of 45 nanohybrid composite plate samples were divided into three groups: the treatment group with pineapple tuber extract gel at pH 2.5 and 6.5, and the control group with 16% carbamide peroxide. The surface roughness of the composite was measured before and after treatment for 14 days using a surface roughness tester. Data analysis was carried out using the Kruskal-Wallis statistical test and the Mann-Whitney post hoc test. The results showed no statistically significant differences in surface roughness between the treatment and control groups (p > 0.05). Although a slight increase in surface roughness was observed following application of pineapple tuber extract gel, the changes were not significant when compared with 16% carbamide peroxide. Pineapple tuber extract gel, as a teeth whitening agent, has no significant effect on the surface roughness of the composite. Therefore, it can be concluded that additional experimental studies are needed before this material can be considered a whitening agent. DOI : 10.54052/jhds.v5n3.p275-288